Sensitivity enhancement in pulse EPR distance measurements - Jeschke, G.; Bender, A.; Paulsen, H.; Zimmermann, H.; Godt, A. (Journal of magnetic resonance (1997), 2004)
Established pulse EPR approaches to the measurement of small dipole–dipole couplings between electron spins rely on constant-time echo experiments to separate relaxational contributions from dipolar time evolution. This requires a compromise between sensitivity and resolution to be made prior to the measurement, so that optimum data are only obtained if the magnitude of the dipole–dipole coupling is known beforehand to a good approximation. Moreover, the whole dipolar evolution function is measured with relatively low sensitivity. These problems are overcome by a variable-time experiment that achieves suppression of the relaxation contribution by reference deconvolution. Theoretical and experimental results show that this approach leads to significant sensitivity improvements for typical systems and experimental conditions. Further sensitivity improvements or, equivalently, an extension of the accessible distance range can be obtained by matrix deuteration or digital long-pass filtering of the time-domain data. Advantages and limitations of the new variable-time experiment are discussed by comparing it to the established analogous constant-time experiment for measurements of end-to-end distances of 5 and 7.5 nm on rod-like shape-persistent biradicals and for the measurement of a broadly distributed transmembrane distance in a doubly spin-labeled mutant of plant light harvesting complex II.